Prevalence of Cerebral Visual Impairment in Children of Health-care Workers in a Tertiary Care Hospital: A Questionnaire-based, Cross-sectional Survey - K. S. Smitha; Mehak Bhutani; Vatsala Prasad; V. Samvedya; Bhagyajyothi B. Khanagavi; Chethana Warad (Journal of the Scientific Society)
Purpose: To estimate the prevalence of cerebral visual impairment (CVI) among children of the health-care workers in our hospital. Methodology: The questionnaire having 25 questions was used to screen all the participants. Participants who answered yes to <5 characteristics were categorized as no risk for CVI, those answering yes to 5–10 characteristics as low risk for CVI, and children answering yes to more than 10 as high risk for CVI. We also evaluated the high-risk red flag characteristics in the form of 5 questions adapted from Dutton’s five-point questionnaire which indicates early features of CVI. Results: Twenty-four percent of the children were diagnosed to have characteristics suggestive of CVI. Eighty-one percent of these children were diagnosed to have low-risk CVI and 19% had high-risk CVI. A total of 6 (5.56%) children demonstrated at least three of the five red flag characteristics of Dutton and were confirmed to have CVI. Conclusion: There is a need for planning of future strategies about increasing awareness regarding CVI among health-care workers in India for early diagnosis and treatment.